1996
DOI: 10.1086/117803
|View full text |Cite
|
Sign up to set email alerts
|

The Final Archive and Recalibration of the International Ultraviolet Explorer (IUE) Satellite

Abstract: Since 1978 the International Ultraviolet Explorer (IUE) satellite has been acquiring the largest collection of astronomical ultraviolet spectra that will likely be obtained in the foreseeable future. The more than 100 000 spectral images, from which low and high dispersion spectra are extracted, include a very broad range of sources from solar system objects, stars of all types, interstellar and Galactic halo gas, normal galaxies, and active galactic nuclei. The Final Archive of IUE data will contain all of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 14 publications
5
94
0
Order By: Relevance
“…We defined an average observed UV spectrum using the available highest S/N ratio spectra, namely LWP 27954 and LWP 30925 for the long wavelength region (1850-3350Å) and SWP 50606 and SWP 50609 for the short wavelength region (1150-2000Å), retrieved from the IUE Final Archive (Nichols & Linsky 1996).…”
Section: Physical Parametersmentioning
confidence: 99%
“…We defined an average observed UV spectrum using the available highest S/N ratio spectra, namely LWP 27954 and LWP 30925 for the long wavelength region (1850-3350Å) and SWP 50606 and SWP 50609 for the short wavelength region (1150-2000Å), retrieved from the IUE Final Archive (Nichols & Linsky 1996).…”
Section: Physical Parametersmentioning
confidence: 99%
“…The log of images are given in Table 2. IUE obtained both low dispersion (6 Å resolution) and high dispersion (λ/δλ ∼ 10 000) spectra with the short-wavelength prime (SWP: 1150-2000 Å), longwavelenght prime (LWP: 1850-3400 Å), and long-wavelength redundant (LWR: 1850-3400 Å) cameras (Nichols & Linsky 1996). The spectra show emission lines originating in the chromosphere and transition region.…”
Section: Iue Data and Spectral Analysismentioning
confidence: 99%
“…29 and Oct. 5, 1984. In this study 54 IUE spectra of σ Gem observed between 1979 and 1986 and reduced by means of NEWSIPS were analysed and some of them were reviewed in detail together with the IUESIPS spectra analysed by Ayres et al (1984) and by Engvold et al (1988). The new calibration together with the new image processing techniques have been summarized by Nichols & Linsky (1996). They pointed out that the wavelength and absolute flux errors in the IUESIPS processing could be corrected by NEWSIPS progressing.…”
Section: Introductionmentioning
confidence: 99%
“…All raw data have been reduced by the NEW SPECTRAL IMAGE PROCESSING SYSTEM (ref. IUE NEWSIPS manual;Nichols & Linsky 1996). In Table 3 we collect the observe time, data format, exposure time, and so on.…”
Section: Observationsmentioning
confidence: 99%